EFFECT OF ORAL ADMINISTRATION OF IgY IMMUNOGLOBULINS ON GROWTH RATE AND INCIDENCE OF DIARRHEA IN DAIRY CALVES - M. Kuczaj; E. Czerniawska-Pitkowska; I. Kowalewska-Auczak; M. Pernak (Journal of Animal and Plant Sciences, 2019)
Among the most common diseases of calves, digestive system diseases, mainly diarrhea are mentioned. Various researchers indicate that the use of IgY from immunized hens can be effective as a protection against calf diarrhea caused by rotavirus infections. The aim of the study was to evaluate the effect of the lyophilisate from hen egg yolks (IgY) orally administered to calves on in their daily body weight gains and the incidence of diarrhea during the first two months of their lives. The study included 40 Polish Holstein-Frisian calves in the large-scale farm located in the Great Poland Province. The formulation containing immunoglobulins of hen egg yolks was administered orally to calves for 8 weeks. On the 0, 28 and 56 day of the life of calves they were weighed to determine the daily weight gains. The frequency of the incidence of diarrhea, their intensity and duration was being determined. The obtained results were analyzed statistically. The significance of differences was calculated using the univariate analysis of variance and performing the test of multiple Duncan's gap using the Statistica®12.5 PL program. Significant differences (P ≤ 0.05) in daily weight gains of the calves in both groups of calves during the first 28 days of life were shown. The administration of IgY had a positive effect on the mitigation of the symptoms of diarrhea, on the reduction in the frequency of their incidence (by 10% in relation to the control group) and on shortening the time of their duration (by 8% less than in the control group). It was found that the introduction of immunoglobulin IgY into calf feeding can positively affect their growth and health condition.
Keywords: calves; daily gain; diarrhea; IgY; yolk immunoglobulin